The effectiveness of revolving door laws: Evidence from government debt management - Filippo Silano (University of Hamburg, Institute of Law and Economics (ILE), 2022)
The increasing presence of the revolving door across several dimensions of statecraft has prompted the introduction of laws addressing the phenomenon's risks. Focusing on executive branches in charge of issuing and managing government debt - debt management units (DMUs) -, this article delivers a case study assessing the effectiveness of revolving door policies, with the overarching purpose of designing regulatory solutions. In government debt management, the revolving door denotes the transition of employees working at the dealers to DMUs, and vice versa. Dealers are financial institutions either appointed by the domestic DMU to participate in auctions of government securities, or exclusively distributing bonds in the secondary market. Drawing on a comparative legal analysis across eight OECD countries and career data from a sample of public debt managers, this study provides empirical evidence that despite legislations curbing the revolving door are in force, the dynamic is free to flow. Reasons are lack of effective monitoring, credible enforcement mechanisms and adequate ethical culture. Addressing shortcomings, policy proposals advocate the establishment of independent oversight bodies endowed with sanctioning power, and measures enhancing the transparency of public officials' career moves. Identifying and plugging loopholes in the framework in force, this study aims at steering policymakers through the ongoing process of modernising conflict of interest regulation.
Keywords: K10; K23; K42; H63; H83; P16; 330; revolving doors; conflicts of interest; public integrity; government debt management; effectiveness of policies; enforcement; regulatory governance